Effect of Short Term High Dose Oral Vitamin D Therapy on the Inflammatory Markers in Patients with COVID 19 Disease - Lakkireddy, Maheshwar; Gadiga, Srikanth Goud; Malathi, RD; Karra, Madhu Latha; Raju, ISSV Prasad Murthy; Ragini; Chinapaka, Sangeetha; KSS, Sai Baba; Kandakatla, Manohar (Archives of Clinical and Biomedical Research, 2022)
Introduction: COVID 19 is known to cause immune dysregulation and vitamin D is a known immunomodulator. This study aims to objectively investigate the effect of short term high dose vitamin D therapy in reducing the inflammatory markers of COVID-19. Materials and Methods: Consented COVID-19 patients with hypovitaminosis D were evaluated for inflammatory markers (N/L ratio, CRP, LDH, IL6, Ferritin) along with vitamin D on 0th day and 9th / 11th day as per their respective BMI category. Subjects were allotted to VD and NVD groups. VD group received Pulse D therapy (a short term high dose supplementation of 60,000 IUs of vitamin D for 8 or 10 days depending upon their BMI) in addition to the standard treatment. NVD group received standard treatment alone. Differences in the variables between the two groups were analysed for statistical significance. Results: Eighty seven out of one hundred and thirty subjects have completed the study (VD:44, NVD:43). Vitamin D level has increased from 15 ng/ml to 81 ng/ml in VD group and highly significant (p<0.01) reduction of all the measured inflammatory markers was noted. Reduction of markers in NVD group was insignificant (p>0.05). The difference in the reduction of markers between the groups (NVD vs VD) was highly significant (p<0.01). Conclusions: Therapeutic improvement in vitamin D to 80-100 ng/ml has significantly reduced the inflammatory markers associated with COVID-19 without any side effects. Hence, adjunctive short term high dose vitamin D therapy can be added safely to the existing treatment protocols of COVID-19 for improved outcomes.